Fuzzy Logic System for Diagnosing Coronary Heart Disease - Salah Mahdi, Mustafa; Faisal Ibrahim, Mohd; Mahmood Mahdi, Shakir; Singam, Praveen; Baseri Huddin, Aqilah (International Journal of Engineering and Technology, 2019)
The diagnosis of coronary heart disease is a non-trivial task that requires a careful and time-consuming examination. Hence, the application of a computer-aided diagnostic (CAD) system to assess the condition of a person of having coronary heart disease is greatly beneficial. Although the usage of CADs related to coronary heart disease diagnosis is widely implemented, the inputs medical data required is still a significant challenge to encourage rapid diagnosis among public. This paper presents a fuzzy logic system for diagnosing coronary heart disease. In this study, the fuzzy logic based CAD system has been developed with five input variables that requires minimal medical procedure to obtain to determine the presence of coronary heart disease. Experiments to assess the accuracy of the system and comparison with a previous work of rough-fuzzy classifier were carried out using an open source coronary heart disease dataset. The results show that the proposed work is able to achieve significant accuracy of 72.6%, an improvement of 30% from the previous work.Â Â